Mining production process innovation : critical success factors to intersystem innovation at Jwaneng Mine Botswana - Mkonto, Strength (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Information Science))--University of Stellenbosch, 2009.